Modelo de avaliação da maturidade da implementação do lean manufacturing com utilização de uma abordagem multicritério linguística - Piaia, Maria Luiza (2019)
As the market became competitive and demanding industries began to worry about managing their processes and meeting the demand, evidencing the need for methods and tools to assist them in decision making. In this context, in order to streamline demand, reduce costs and improve production control, companies are looking to implement Lean Manufacturing (LM), which is a management system aimed at eliminating activities that do not add up value to the product, or process, and make processes more agile and flexible. It is understood that the simple implementation of the LM tools does not guarantee that the performance is the best possible. Based on the increasing search for LM Implementation, it was verified the need to develop new instruments to measure the level of maturity that these companies are in relation to LM practices, and that, in addition, allows to better evaluate in which stage they are , classifying them as basic, intermediate and advanced level. It is known that the measurement broadens the organization's awareness of Lean deployment. This greater awareness "tends" to imply new efforts and gains in the productive system. In this scenario, this study aims to propose a model that evaluates the degree of maturity of the LM implementation in companies, including in a quantitative way, using the multicriteria approach. Regarding LM, the 2 Tuple methodology enables managers to identify critical points and make decisions in uncertain situations, also allowing an instantaneous and comprehensive view of strong areas and those in need of improvement. In the same way, it allows the directing of actions for a structured and effective implementation, contributing to the development of the companies. The accomplishment of this study is justified by the difficulty in the evaluation of the LM implantations, mainly in its degree of maturity, besides its practices. The maturity model was applied in three companies, in which feedback was generated in relation to the LM performance for each company. The contribution of this work was to create a maturity evaluation model that also had the ability to evaluate each criterion individually, making it possible to visualize the deficiencies that need improvement actions.